The Factor Testing of Indicators of Physical and Functional Preparation of Basketball Players - Thuc, Dao Chanh (Journal of Sports Research, 2018)
The problem of physiological study of non-traditional means of coaching attracts a lot of scientists’ attention in recent years. This is due to the need to provide a maximum development of certain muscle groups and direction of the coaching process. Proper use of simulators weight machines bring positive results (Valeria et al., 2018). Obviously, an important step in the use of technology is the right choice for team sports coaches and personal trainers for the effectiveness of the coaching process. One effective component of this process is the inclusion to a coaching program with the help of physical exercises would be TRX® function loops. Among specialists of functional and physical coaching innovation as TRX® – coaching is one of the best equipment for complex solution of the tasks. This exercise is an exercise using body weight. It was designed to develop strength, power, core stability, flexibility and balance. TRX® is the valuable creation for the sports industry of any levels. TRX® Coaching –Suspension Coaching became commonly usable for Fitness Health Clubs, Professional Sports and Elite Strength Conditioning Workout for Sports Teams (Dao and Le, 2018). Therefore, it was suggested the use of TRX® exercises in preparation of basketball players. The results of the study clearly show that the inclusion in the 18-25 years old basketball player coaching program with the TRX® functional loop contributes to a significant increase in overall fitness levels and ability to foster gas of life. Using TRX® during coaching can be considered to be an important factor in increasing the effectiveness of basketball preparation.